2015
DOI: 10.1186/s12889-015-1736-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of a 3-month workplace-based pedometer-driven walking programme on health-related quality of life in meat processing workers: a feasibility study within a randomized controlled trial

Abstract: BackgroundIn New Zealand, meat processing populations face many health problems as a result of the nature of work in meat processing industries. The primary aim of this study was to examine the feasibility of using a pedometer-based intervention to increase physical activity and improve health-related outcomes in a population of meat processing workers.MethodsA single-blinded randomized controlled trial (RCT) was conducted. A convenience sample of meat workers (n = 58; mean age 41.0 years; range: 18-65) partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 87 publications
6
44
0
1
Order By: Relevance
“…For example, participants in our study saw the benefits of physical activity awareness via self-monitoring and goal-setting. This mirrors the results of a randomized controlled trial that found an intervention based on self-monitoring to be effective in increasing physical activity [38]. Furthermore, we found that non-users expected WATs to track diverse activities and were disappointed that the technology did not do it.…”
Section: Comparison With Prior Worksupporting
confidence: 82%
“…For example, participants in our study saw the benefits of physical activity awareness via self-monitoring and goal-setting. This mirrors the results of a randomized controlled trial that found an intervention based on self-monitoring to be effective in increasing physical activity [38]. Furthermore, we found that non-users expected WATs to track diverse activities and were disappointed that the technology did not do it.…”
Section: Comparison With Prior Worksupporting
confidence: 82%
“…The intervention group showed a significant increase in steps at 3 months and significant decreases in BMI, body fat, and waist circumference. Importantly, these results remained significant 3 months after the completion of the intervention (38). Of note, these effects may have been due to other behavior change elements in addition to goal setting.…”
Section: Strategies For Promoting Behavior Changementioning
confidence: 95%
“…A recent randomized controlled trial used self-monitoring and goal setting to increase steps over 3 months (38). Half of the participants were asked to use a pedometer to self-monitor their walking, with goals of increasing their steps by 5% weekly.…”
Section: Strategies For Promoting Behavior Changementioning
confidence: 99%
“…In this study, average ESE scores are higher when compared to a similar New Zealand age group cohort (Mansi et al 2015). It should be noted, however, that the referenced cohort, unlike those in our study, was derived from a rural community as a part of a pedometer-driven walking programme (Mansi et al 2015).…”
Section: Discussionmentioning
confidence: 56%
“…It should be noted, however, that the referenced cohort, unlike those in our study, was derived from a rural community as a part of a pedometer-driven walking programme (Mansi et al 2015). Substantial literature supports that higher self-efficacy beliefs are associated with positive health behaviours including initiation and adherence to exercise (Delahanty et al 2006, Kosma et al 2004, McAuley 1993.…”
Section: Discussionmentioning
confidence: 88%